Some Efficiency Aspects of Monopolistic Competition: Innovation, Variety and Transaction Costs - TODOROVA, Tamara (Theoretical and Practical Research in Economic Fields, 2021)
We stress some efficiency aspects of monopolistic competition justifying it on account of its tendency to innovate and the questionable excess capacity paradigm. Some further efficiency aspects revealed are product variety and transaction cost savings. We view the monopolistically competitive firm as an essential source of technological innovation, product variety and cost economies. While perfect competition is universally considered a benchmark and a social optimum, we consider it a strongly unrealistic theoretical setup where the monopolistically, rather than the perfectly, competitive firm turns out to be the true type of competition and social optimum in the real world of positive transaction costs. The monopolistically competitive firm not only offers product variety and innovation but is the optimal institutional arrangement under positive transaction costs.